ANALISIS YURIDIS KEWENANGAN PENYIDIK PEJABAT PEGAWAI NEGERI SIPIL BEA CUKAI DAN PENYIDIK POLRI DALAM TINDAK PIDANA PENYELUNDUPAN NARKOTIKA - Adelia Apriyanti; Ilham Abbas; Baharuddin Badaru (Qawanin Jurnal Ilmu Hukum, 2020)
The research aims to: 1) Know the role of civilian state officials as investigators in the crime of narcotics smuggling in the border areas of the Republic of Indonesia and Papua New Guinea, and 2) Know the obstacles for investigators of civilian officials in the implementation of countermeasures for narcotics smuggling in the border areas of the Republic of Indonesia. and Papua New Guinew. This research qualifies into the type of sociological or empirical legal research, namely legal research using secondary data as initial data, which is then followed by primary data in the form of data obtained from interviews in this case Civil Servant Investigators from the Customs and Excise Office and the City Police. Jayapura Papua, then a qualitative analysis was carried out. The results of this study indicate: The role of the Customs and Excise Civil Servant Investigators in handling the criminal act of smuggling narcotics in the type of marijuana in the border area of ​​the Republic of Indonesia with Papua New Guinew, has been carried out well, as evidenced by the number of cases of drug smuggling that have been arrested. Factors that hinder investigators of Customs and Excise Civil Servants in dealing with the criminal act of smuggling of Cannabis Narcotics in the Border Area of ​​the Republic of Indonesia and Papua New Guinea are due to the large area and lack of Civil Servant Investigators, there is no understanding with law enforcement agencies. other, as well as the lack of adequate facilities and infrastructure. Recommendations for this research: In the future it is necessary to carry out cross-agency and cross-country cooperation in the form of information exchange, technical assistance, namely: technology-tools, experts, training and joint operation activities, and it is hoped that the Directorate General of Customs and Excise will further tighten supervision, improve intensity of patrols, implementing Customs and Excise administration provisions consistently because drug smuggling cases are very detrimental.